Digestion, Purification, and Enrichment of Protein Samples for Mass Spectrometry. Issue 3 (1st September 2015) - Hedrick, Victoria E.; LaLand, Mercedes N.; Nakayasu, Ernesto S.; Paul, Lake N.
Abstract : Proteomic studies rely heavily on the use of liquid chromatography (LC)–mass spectrometry (MS and MS/MS) analyses to provide information about protein composition and function. Profiling the proteome can be the first step to understanding biological pathways, but the challenges scientists face with the complex nature of proteins and proteolysis products can be daunting. Techniques involving fractionation, immunoprecipitation, and phosphopeptide enrichment can simplify complex protein mixtures and enhance the amount of target proteins that are important to the investigator. Emphasis on sample preparation for LC‐MS/MS analyses is essential to acquisition of high‐quality data for proteomic research. Certain classes of reagents, materials, and contaminants that can be introduced during sample processing may limit the effectiveness of LC‐MS/MS analysis. These protocols outline methods for proteolytic digestion of proteins that are compatible with LC‐MS/MS, along with procedures that allow for simplification of complex protein matrices. © 2015 by John Wiley & Sons, Inc.